Early postoperative complications after lung transplantation - I. V. Pashkov; V. N. Poptsov; D. O. Oleshkevich; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2019)
Lung transplantation is the final treatment option for end-stage lung disease when all possible conservative treatment is exhausted. According to the International Society for Heart and Lung transplantation Registry, more than 60000 lung transplantations have been performed worldwide. The early post-transplant period following lung transplantation remains critical because of numerous complications. These complications can be divided into several groups. These are surgical complications, primary graft dysfunction and acute rejection, infection, cardiovascular, abdominal and renal disorder. This complications may result in significant morbidity, mortality and limit short and long-term survival. The aim of this review is to describe the main postoperative complications in first month after lung transplantation in the world practice.